2016
DOI: 10.5005/jp-journals-10006-1437
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Maternal Mortality in Baba Raghav Das Medical College, Gorakhpur

Abstract: Introduction Prevention of maternal deaths is one of our foremost goals to provide safety to motherhood and to avoid loss to the family, society, and the nation. Maternal mortality ratio (MMR) of Uttar Pradesh is very high as compared to national average. Within the state, there is wide variation in MMR. The explanations and answers to these regional variations are complex. This study was planned with the objectives to explore each and every maternal death that had occurred in Baba Raghav Das Medical College i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Stroke comprises both hemorrhagic and ischemic etiologies, with 38% of the cases were found to be of hemorrhagic, most commonly being secondary to aneurysm followed by the rupture of arteriovenous (AV) malformation. 3 Many populationbased studies have shown an increased risk of hemorrhagic stroke in women with hypertension due to PE. Takahashi et al noted that pregnancies with hypertensive disorders had a 12% incidence of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke comprises both hemorrhagic and ischemic etiologies, with 38% of the cases were found to be of hemorrhagic, most commonly being secondary to aneurysm followed by the rupture of arteriovenous (AV) malformation. 3 Many populationbased studies have shown an increased risk of hemorrhagic stroke in women with hypertension due to PE. Takahashi et al noted that pregnancies with hypertensive disorders had a 12% incidence of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive disorders of pregnancy were reported to be the most common cause of maternal mortality in other studies also. 10,28 Limitations of the study…”
Section: Maternal Outcomesmentioning
confidence: 99%